THE INFLUENCE OF CONTENT MARKETING AND INFLUENCER MARKETING ON PURCHASE DECISIONS - Nurani; Bondan Subagyo; Rosa Aprilia Ika Rahayu (BEMJ : Business, Entrepreneurship, and Management Journal, 2024)
The increasing number of TikTok application users makes an extraordinary difference. Starting from the realm of short entertainment videos, TikTok is expanding into the realm of e-commerce (TikTok Shop). Not a few TikTok users make purchasing decisions through TikTok Shop. Marketing techniques, including content and influencer marketing, influence purchasing decisions at TikTok Shop. This study aims to determine the partial or simultaneous influence of Content and Influencer Marketing variables on purchasing decisions at TikTok Shop. The research method used is quantitative, using p, primary data in questionnaires by dist.uThennaires to 84 were distributed to students of the Faculty of Economics, Tulungagung University. The calculation uses the SPSS 16 program. The study results indicate that content and influencer marketing variables positively and significantly affect the purchasing decisions of students who use TikTok Shop, Faculty of Economics, Tulungagung University. Simultaneously, the content marketing and influencer marketing variables positively and significantly affect the purchasing decisions of students who use TikTok Shop, Faculty of Economics, Tulungagung University.